REVOLUSI INDUSTRI 4.0: DESAIN PERKEMBANGAN TRANSAKSI DAN SISTEM AKUNTANSI KEUANGAN - Prajanto, Agung; Pratiwi, Ririh Dian (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
The Industrial Revolution 4.0 has changed the human perspective in interacting and doing business fundamentally. Business systems that are transformed into online systems have an impact on the way humans conduct financial transactions. Principles contained in Industry 4.0. provide an illustration that interconnection with the internet and good data security will result in the provision of fast information to produce decisions. The study uses a literature study approach that examines data and information from journals, textbooks, and he internet to conduct a deeper study of the application of industry principles 4.0 to financial transactions and accounting. based on the results of the study concluded that the financing transaction media had developed into the Fintech industry and the transaction system in the form of a payment gateway. The large number of financial transactions with the payment gateway system requires companies to do IT Spending intangible asset in the form of Big Data and Cloud Computing security systems. The technology provides benefits for the company in terms of data analysis and provision of information to speed up the decision making process and secure storage systems and affordable costs. Through the information technology media, it will facilitate management to make decentralized decision making.